Magnetocaloric effect in the spin-1/2 Ising-Heisenberg diamond chain with the four-spin interaction - Gálisová, L. (Condensed Matter Physics, 2014)
The magnetocaloric effect in the symmetric spin-1/2 Ising–Heisenberg diamond chain with the Ising four-spin interaction is investigated using the generalized decoration-iteration mapping transformation and the transfer-matrix technique. The entropy and the Grüneisen parameter, which closely relate to the magnetocaloric effect, are exactly calculated to compare an ability of the system to cool in the vicinity of different field-induced ground-state phase transitions during the adiabatic demagnetization.